Efficiency of application of innovative technologies in the organization of practical training - N. I. Taraseeva; O. V. Baulina (Открытое образование (Москва))
The article discusses the effectiveness of creating a network site as a mechanism to ensure the quality of training, allowing to introduce innovative and practical activities in the educational process, developing the scientific potential of educational institutions, both in secondary vocational education and in institutions of higher professional education.The purpose of the study is aimed at practical training both at the stage of training highly qualified specialists in secondary vocational schools (SVS) and higher education (VO), including through networking.The authors, on the basis of their practical experience, propose to consider the creation of a network site based on educational institutions as a project oriented towards obtaining professions and specialties demanded by the construction industry with the aim of introducing an inventive, creative idea into the process of theoretical and practical training, as well as successful socialization of the younger generation.When performing this work, analysis methods, design method and practice method were used.The main material of the article is the School-College-University-Enterprise network interaction model, which allows educational institutions not only to survive, but also to develop dynamically, flexibly adapting to modern changes in the labor market conditions, the requirements of scientific and technological progress and the state economy. For this purpose, regional network sites are being created on the basis of educational institutions not only for practical training, but also for holding the WorldSkills Russia regional championship. To form a network site, educational institutions should establish business cooperation with potential employer partners, with schools in the city of Penza and the Penza region. The creation of network centers in educational organizations is a social innovation and becomes one of the priorities in the field of modern education.The distance education system in the form of an electronic educational environment, introduced at the Penza State University of Architecture and Construction, enables full-time and part-time students to independently study the necessary part of the material and also remotely (in the form of tests or online dialogue) to carry out self-certification and certification for the disciplines studied . Graduates with a secondary vocational education and enrolled in a higher education institution have an insignificant, but already practical work experience in their specialty, and a certain knowledge base. Interactive capabilities of the electronic educational environment of the university make it possible to obtain the necessary information at a convenient time and in any place (on the construction site during free time from work, etc.) and return to the training material several times. The rich experience of university professors allowed developing the necessary documentation in all areas of training, taking into account the results of scientific research and practical experience.According to the results of the research, the article presents data that allows teachers and students to carry out (during the training and work experience) and improve the graduate’s professional activities, expand the field of knowledge, and also shape the innovative potential of educational institutions. As part of the program to create a regional network site, work is underway to develop and implement mechanisms for the state order for personnel training, to expand the forms and methods that encourage students to achieve high results. In conclusion, it can be noted that network interaction allows to overcome the closeness of institutions of different levels, to carry out cooperation on the rights of partnership, to build strong and effective communication in the preparation of highly qualified specialists.